Prevalence of Musculoskeletal Pain in Construction Workers in Saudi Arabia - Ahmad Alghadir; Shahnawaz Anwer (The Scientific World Journal)
The objective of this study was to find out the prevalence, characteristics, and distribution of musculoskeletal pain among construction workers in Saudi Arabia. A questionnaire about musculoskeletal pain in different parts of the body was completed by 165 construction workers from the construction industries in Dammam and Riyadh cities. The descriptive data were analyzed using chi-square test. The level of statistical significance was set at P<0.05. Eighty (48.5%) of the responding workers had pain in neck, shoulders, lower back, hand, knee, or ankle. The majority of respondents had low back pain (50%) followed by knee pain (20%). The average intensity of pain at all sites during activity and rest was 6.65 and 3.59, respectively. Thirty-four (42.5%) respondents had dull aching pain and 24 (30%) had cramping pain. There was an association between years of experience, duration of break during work, and use of protective equipment with the prevalence of musculoskeletal pain in construction workers (P<0.05). Most of the workers complaining of pain got medical treatment (62.5%) and only 25% received physical therapy. It can be concluded from this study that the prevalence of musculoskeletal pain among construction workers in Saudi Arabia is high.